HUBUNGAN TINGKAT KEGAWATAN DENGAN LAMA TINGGAL PASIEN DI IGD RSU GMIM KALOORAN AMURANG - Bidjuni, Hendro; Kundre, Rina (JURNAL KEPERAWATAN, 2017)
Abstract : The emergency patient service is a services that requires immediately relief including quick, accurate and careful to prevent death and disability, or the emergency patient service takes a very important role that time is about life. The length of stay is the time the patient arrives at the emergency room and performed the initial assessment to the handling during in the ER but in a short time.The purpose of this research is to analyze the relations of criticalness with the length of stay of patient in the emergency installation of GMIM Kalooran Amurang’s general hospital. Research methods applying cross sectional. The sampling techniques of these research are purposive sampling with total samples 98. The data collection using observation sheet. Data processing using SPSS with Spearman test with the significant level 90 % ( α = 0.010). The results using Spearman analysis shows that there’s no correlation of criticalness with the length of stay ( p = 0.195 ). The conclusion is there’s no relations of criticalness with length of stay in the emergency installation of GMIM Kalooran Amurang’s general hospital. The suggestion for a nurse to still treating patient who is in emergency installation appropriate to criticalness and quick time. Key Word : Criticalness, Length of Stay Abstrak : Pelayanan pasien gawat darurat adalah pelayanan yang memerlukan pertolongan segera yaitu cepat, tepat dan cermat untuk mencegah kematian dan kecacatan, atau pelayanan pasien gawat darurat memegang peranan yang sangat penting bahwa waktu adalah nyawa. Lama tinggal adalah waktu pasien tiba di IGD dan dilakukan pengkajian awal sampai pada penanganan selama di IGD tapi dalam waktu yang singkat. Tujuan penelitian ini untuk menganalisa hubungan tingkat kegawatan dengan lama tinggal pasien di IGD RSU GMIM Kalooran Amurang. Metode penelitian yaitu dengan rancangan cross sectional study. Teknik pengambilan sampel pada penelitian ini yaitu purposive sampling dengan jumlah 98 sampel. Pengumpulan data dilakukan dengan menggunakan lembar observasi. Pengolahan data menggunakan program SPSS dengan uji spearman dengan tingkat kemaknaan 90% (α = ,010). Hasil penelitian dengan menggunakan analisis spearman menunjukkan tidak terdapat hubungan tingkat kegawatan dengan lama tinggal (p = 0,195). Kesimpulan tidak ada hubungan tingkat kegawatan dengan lama tinggal di IGD RSU GMIM Kalooran Amurang. Kata kunci : Tingkat kegawatan, Lama Tinggal